Reflections from a humble and much revered Wimbledon Champion - Young, J. A.; Pearce, A. J. (Coaching and Sport Science Review, 2022)
This paper reports on a review of the post-match interviews with the Australian Ash Barty during the 2021 Wimbledon Championships. Seven transcripts were inductively content analysed to reveal six dominant themes. The analysis provides insight into Barty`s mindset and highlights the importance of her coach, support team and role model. Implications for coaches to adhere to sound coaching principles are discussed.